2018
DOI: 10.3390/ijms19010130
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Aquaporins and Hypomethylation: Potential Implications for Atherosclerosis and Cardiovascular Disease

Abstract: Aquaporins (AQPs) are transmembrane channels that facilitate water and glycerol permeation through cell membranes. Recently, the water channel AQP1 was suggested to contribute to endothelial homeostasis and cardiovascular health. Less is known about endothelial aquaglyceroporins expression and its implication in cardiovascular disease (CVD). We have previously used cultured human endothelial cells under a hypomethylating environment to study endothelial dysfunction and activation, a phenotype implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
(87 reference statements)
0
25
0
2
Order By: Relevance
“…Previous studies reported the experimentally calculated permeability values for water and glycerol permeation via different AQPs, including AQP3, in different cells. 1,[24][25][26] Moreover, a few studies also included hydrogen peroxide transport rates via AQP3. 14,27 In general, permeability values for water are in the order of 10 À3 cm s À1 , while glycerol and H 2 O 2 are in the range of 10 À6 cm s À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported the experimentally calculated permeability values for water and glycerol permeation via different AQPs, including AQP3, in different cells. 1,[24][25][26] Moreover, a few studies also included hydrogen peroxide transport rates via AQP3. 14,27 In general, permeability values for water are in the order of 10 À3 cm s À1 , while glycerol and H 2 O 2 are in the range of 10 À6 cm s À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The superoxide further evolves, leading to the generation of different ROS and, lastly, ending up with hydrogen peroxide production. It has been reported that extracellular H 2 O 2 can cross the plasma membrane through aquaporin AQP3, thereby triggering intracellular ROS signaling ( 47 , 48 ). In line with our previous results, we have demonstrated here that intracellular ROS enhancement does occur in ECFCs upon photoexcitation of polymer thin films, thus contributing to TRPV1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The relative quantification of gene expression was determined using the 2 Ct method based on a Livak method modification [62]. AQP gene expression was normalized to the mean of two housekeeping genes (HPRT-1 and β-actin) [63]. This procedure was performed in triplicate.…”
Section: Rna Isolation Cdna Synthesis and Quantitative Pcrmentioning
confidence: 99%